2013
DOI: 10.3354/dao02620
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Vietnamese and US isolates of Edwardsiella ictaluri

Abstract: We compared Edwardsiella ictaluri from striped catfish in Vietnam with US channel catfish isolates. Biochemical analyses and sequencing of the 16S rRNA gene confirmed that the Vietnamese isolates were E. ictaluri. Comparison using rep-PCR fingerprinting demonstrated no significant differences between the isolates, but plasmid analysis indicated that the Vietnamese isolates grouped into 4 plasmid profiles, each different from the typical pEI1 and pEI2 plasmid profile found in the US isolates. Sequencing plasmid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 37 publications
(36 reference statements)
5
52
0
Order By: Relevance
“…Sharing the same diseased pattern with channel catfish (I. punctatus) in the United States, E. ictaluri and F. columnare have been reported as the most highly pathogenic bacteria threatening the cultured striped catfish industry in Vietnam (Crumlish et al, 2002;Ferguson et al, 2001;Tien et al, 2012). Recent reports, however, have indicated that the genetic characterization and pathogenicity of E. ictaluri were different between Vietnamese and US isolates (Bartie et al, 2012;Rogge et al, 2013), where E. ictaluri catfish isolates from Vietnam were nonpathogenic to the US channel catfish (Rogge et al, 2013). The differences in clinical signs and histopathological manifestations caused by E. ictaluri in two different hosts may explain the inconsistency in originally described names as enteric septicemia of catfish (ESC) in US channel catfish and "bacillary necrosis in Pangasius" in Vietnamese striped catfish (Crumlish et al, 2002;Ferguson et al, 2001;Hawke et al, 1981).…”
Section: Discussionmentioning
confidence: 95%
“…Sharing the same diseased pattern with channel catfish (I. punctatus) in the United States, E. ictaluri and F. columnare have been reported as the most highly pathogenic bacteria threatening the cultured striped catfish industry in Vietnam (Crumlish et al, 2002;Ferguson et al, 2001;Tien et al, 2012). Recent reports, however, have indicated that the genetic characterization and pathogenicity of E. ictaluri were different between Vietnamese and US isolates (Bartie et al, 2012;Rogge et al, 2013), where E. ictaluri catfish isolates from Vietnam were nonpathogenic to the US channel catfish (Rogge et al, 2013). The differences in clinical signs and histopathological manifestations caused by E. ictaluri in two different hosts may explain the inconsistency in originally described names as enteric septicemia of catfish (ESC) in US channel catfish and "bacillary necrosis in Pangasius" in Vietnamese striped catfish (Crumlish et al, 2002;Ferguson et al, 2001;Hawke et al, 1981).…”
Section: Discussionmentioning
confidence: 95%
“…[21,77,78,79,80,81,82,83]. These publications included research related to fish (6) and shrimp farms (2).…”
Section: Resultsmentioning
confidence: 99%
“…These publications included research related to fish (6) and shrimp farms (2). All publications came from Thailand and Vietnam, even though four investigated aquaculture samples originating from several SEA countries (Thailand, Vietnam, Malaysia, and Indonesia) [78,79,80,82]. One study investigated AMR in isolates from imported aquaculture products from Thailand.…”
Section: Resultsmentioning
confidence: 99%
“…Another factor potentially affecting vaccine efficacy is antigenic variability among virulent isolates. Although E. ictaluri is for the most part considered a serologically homogenous species (Plumb and Vinitnantharat 1989;Bertolini et al 1990;Lobb et al 1993), recent evidence suggests isolates recovered from different host species and different geographical regions have variable genetic and antigenic profiles (Soto et al 2012;Hawke et al 2013;Rogge et al 2013). In addition, during cross-challenge studies, Channel Catfish immunized using a panel of E. ictaluri isolates did not exhibit uniform protection against all heterologous isolates used in the study .…”
Section: Discussionmentioning
confidence: 96%